Assessment of Suitable Reference Genes for Quantitative Gene Expression Studies in Melon Fruits - Kong, Qiusheng; Gao, Lingyun; Cao, Lei; Liu, Yue; Saba, Hameed; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2016)
Melon (Cucumis melo. L) is an attractive model plant for investigating fruit development because of its morphological, physiological, and biochemical diversity. Quantification of gene expression by quantitative reverse transcription PCR (qRT-PCR) with stably expressed reference genes for normalization can effectively elucidate the biological functions of genes regulating fruit development. However, the reference genes for data normalization in melon fruits have not yet been systematically validated. In this study, 20 candidate reference genes were assessed for their potential use as reference genes in melon fruits. GeNorm and NormFinder analyses showed that Cytosolic ribosomal protein S15 (CmRPS15) was the preferred single reference gene. While, CmRPS15 and Ribosomal protein L (CmRPL), or RAN GTPase (CmRAN) and TATA-box binding protein (CmTBP2) were the suitable reference gene combinations in melon fruits. Reliabilities of these identified genes was further validated by the parallel analyses of sucrose contents, activities of soluble acid invertase (AI) and sucrose phosphate synthase (SPS), and expression profiles of their respective encoding genes CmAIN2 and CmSPS1 during melon fruit ripening. These validated reference genes will help to improve the accuracy of gene expression quantification in melon fruits.